STK3-ALK, a Novel ALK Rearrangement in Non-Small Cell Lung Cancer With Sensitivity to Tyrosine Kinase Inhibitors: A Case Report - Feng, Chunlai; Zhou, Rong; Liu, Feng; Wang, Tingting; Liu, Sisi; Shao, Yang (Frontiers in Oncology, 2021)
Anaplastic lymphoma kinase (ALK) rearrangement occurs in 5% to 8% of patients with non–small cell lung cancer (NSCLC). More than 90 different ALK fusion partners have been discovered in NSCLC patients, and ALK tyrosine kinase inhibitors (TKIs) such as crizotinib and alectinib have achieved tumor responses in patients with advanced ALK-positive NSCLC. Here, we report the case of a patient with an advanced NSCLC carrying a novel serine/threonine kinase 3 (STK3)-ALK rearrangement which was identified by targeted next-generation sequencing (NGS), and was confirmed by RNA sequencing. Anti-ALK immunohistochemistry staining (IHC) also revealed the high expression of ALK. The patient benefitted from alectinib treatment after experiencing crizotinib resistance, and achieved an overall response to TKI of over 14 mouths. At the timepoint of submission of this manuscript, this patient is still receiving alectinib treatment with a good tolerance. This study provides meaningful insight into the potential treatment option for NSCLC patients with brain metastases harboring STK3-ALK fusions, and highlights the advantages of NGS in rapidly identifying novel molecular targets.